Integrated cash waqf micro-enterprise support model for enhancing refugee livelihood - Kachkar, Omar; Mohammad, Mustafa Omar; Saad, Norma; Kayadibi, Saim (Islamic Cultural Centre, 2016)
Refugee crisis has recently become the focus of international discourse, especially in the wake of the recent influx of the Syrian refugees. According to the latest UNHCR report issued in June 2016, the number of displaced people reached 65.3 million including 21.3 refugees (UNHCR, 2016). Most of the new refugees, like their predecessors in millions, will end up stuck in camps or temporary settlements for decades. Durable solutions proposed by UNHCR, notably repatriation, integration in local population and resettlement in a third country, have proven ineffective, insufficient and inaccessible for the majority of refugees. An alternative solution of economic engagement for refugees was proposed. This has also remained out of reach to the majority of refugees, mainly owing to legal constraints, discouraging policies of host countries and lack of funds for NGOs to support refugee micro-enterprises. Lack of access to finance and markets remains the prime challenge for refugees wishing to start microenterprises. A new institution and viable model has become imperative. This study employs cash waqf to develop a micro-enterprise support model for refugees (CWMES-R). The model addresses the main challenges of finance, marketing services and training in order to support refugee microenterprises.